Tectonic constraints on 1.3 similar to 1.2 Ga final breakup of Columbia supercontinent from a giant radiating dyke swarm - Hou, Guiting; Santosh, M.; Qian, Xianglin; Lister, Gordon S.; Li, Jianghai (Gondwana Research, 2008)
The 1.3- 1.2 Ga fan- shaped Mackenzie dyke swarm and other similar- aged dyke swarms in the Canadian Shield constitute the subswarms of a Late Mesoproterozoic giant radiating swarm. The Late Mesoproterozoic mafic dyke swarms in Australia and East Antarctica might constitute additional subswarms of the giant radiating dyke swarm. A possible Late Mesoproterozoic mantle plume is placed at the focal area of the giant radiating dyke swarm between North America and the landmass (West Australia- East Antarctica). This mantle plume triggered the continuous extension at ca. 1.3-1.2 Ga, which extended into much of Columbia and led to the final fragmentation of the Columbia supercontinent. Crown Copyright (C) 2008 Published by Elsevier B.V. on behalf of International Association for Gondwana Research. All rights reserved. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000258812500021&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 59 LETTER 3 561-566 14